Nurses' knowledge of heart failure self‐care education: A systematic review. Issue 2 (2nd February 2022) - Chi, Suh Yenn; Soh, Kim Lam; Raman, Rosna Abdul; Ong, Swee Leong; Soh, Kim Geok
Abstract: Background: The prevalence of heart failure is increasing, associated with high mortality and rehospitalization rate. The complexity and progressive clinical syndromes of heart failure have massively affected patients' quality of life. Heart failure self‐care education provided by nurses seems to improve patients' knowledge and the clinical outcomes despite being in critical care or community settings. Nurses often gained heart failure self‐care knowledge from formal and informal educational resources. However, the extent of knowledge acquired by nurses needs to be investigated before patient education could be successfully carried out. Aims: This systematic review identified the nurses' knowledge of heart failure self‐care education according to the topics and factors that would be substantial to increase their knowledge. Methods: Literature resources from Medline, CINAHL, Ovid, Science Direct, Scopus and Google Scholar from 2002 to 2020 were studied and reviewed. This systematic review included nurses that take care of heart failure patients and studies that measured their knowledge score. The quality of all studies was determined using the JBI SUMARI Critical Appraisal tool, and a narrative approach was used to analyse the results. Results: 15 studies were selected, involving 1644 nurses that had experience in taking care of heart failure patients. The overall mean ± SD score of nurses' knowledges was unsatisfactory with 12.1 ± 2.7 to 17.3 ± 1.4, respectively, and it showed a significant increase in the level of knowledge after attending a heart failure speciality course or educational intervention. The majority of the nurses were uncertain about the deteriorating symptoms and fluid management for heart failure patients. Conclusions: The nurses' level of knowledge was unsatisfactory, and therefore they need more in‐depth learning and understanding of the heart failure topic through educational interventional. Relevance to Clinical Practice: Critical care nurses needed to have in‐depth knowledge to recognize symptoms of deterioration in heart failure patients, especially during the decompensated stage.